KARAKTERISTIK PENDERITA THALASSEMIA DI RSU SARI MUTIARA MEDAN TAHUN 2012-2014 - jane ruby tomita; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTThalassaemia is a hereditary blood disorder caused by deficiency of the formation of alpha or beta globin chains that make up haemoglobin. According to WHO, there were approximately 5% of the world’s population carry the genetics and 370.000 babies were born with this disorder every year. The prevalence of Thalassaemia carrier in Indonesia 3-8%, the national prevalence of Thalassaemia in Indonesia is 0,1%. In North Sumatera, the prevalence of Alpha Thalassaemia 3,35% and 4,07% Beta Thalassaemia.This was a descriptive research using case series design, to determined the characteristics of Thalassaemia patients in RSU Sari Mutiara Medan 2012-2014. The population were 71 cases of Thalassaemia data which registered in RSU Sari Mutiara Medan 2012-2014.This research showed that highest characteristics proportion of Thalassaemia patients at age group 6-11 (35,2%), male (57,7%), Javanese (64,8%), Islam (38,0%), come from outside of Medan (56,3%), pale as a major symptomp (63,4%), Thalassaemia Beta (87,3%), had blood transfusion and medicamentosa (73,2%), the number of visits in one month is once a month (78,9%), and cost source from others (95,8%). It is significant between medical management of Thalassaemia patients and type of Thalassaemia.To everyone who find these kind of symptom such aspale face, fatigue, bigger abdoment and genetically patented by Thalassaemia, please go to the nearby hospital as soon as possible. Routine check up and having a general genetic premaried counseling are suggested to ones who suffered Thalassaemia.